Family physicians’ questions about the COVID-19 pandemic: a content analysis of 2,272 helpline calls - McDougall, Allan; Fortier, Jacqueline H.; Zhang, Cathy; Ehrat, Caroline; Best, Kerri; Blois, Heather; Garber, Gary (Université d'Ottawa | University of Ottawa, 2023)
Abstract Background During the COVID-19 pandemic, family physicians faced challenges including travel restrictions for patients, lockdowns, diagnostic testing delays, and changing public health guidelines. Given that 95% of Canadian physicians are members of the Canadian Medical Protective Association (CMPA), the CMPA’s telephone helpline — which offers peer-to-peer support — provides valuable insights into family physicians’ experiences during the pandemic. Methods We used a content analysis approach to identify and understand family physicians’ questions and concerns related to the COVID-19 pandemic expressed during calls to the Canadian Medical Protective Association (CMPA) telephone helpline. Calls were classified with preliminary codes and subsequently organized into themes. We collected aggregated data on calls, including province, call date, and whether the physician self-identified having hospital-based activities as part of their practice. Findings from the analysis were explored alongside family physician calls per month (call volume). Results Between 01 and 2020 and 31 December 2021, 2,272 family physician calls related to the pandemic were included for content analysis. We identified six major themes across these calls: challenging patient interactions; COVID-related care; the impact of the pandemic on the healthcare system; virtual care; physician obligations and rights; and public health matters. COVID-related call volumes were highest early in the pandemic especially among physicians without major hospital affiliation when family physicians practiced with little guidance on how to balance patient care and scarce resources in the face of a novel pandemic. Conclusions This research provides unique insight on the effects the COVID-19 pandemic had on family medicine in Canada. These results provide insights on the needs and information gaps of family physicians in a public health crisis and can inform preparedness efforts by public health agencies, professional organizations, educators, and practitioners.